Whither Agroforestry Sans Policy - the Indian Context - Kishwan, Jagdish (Indian Forester, 1995)
Two third of our population is still dependent on agriculture and forestry, therefore proper development of agroforestry is must for ensuring food security as well as ecological stability. The present paper emphasises the immediate need for drafting a national agroforestry policy alongwith some suggestion for a suitable policy framework.